Divalent, trivalent, and heavy fermion states in Eu compounds. Issue 36 (22nd December 2017) - Ōnuki, Y.; Nakamura, A.; Honda, F.; Aoki, D.; Tekeuchi, T.; Nakashima, M.; Amako, Y.; Harima, H.; Matsubayashi, K.; Uwatoko, Y.; Kayama, S.; Kagayama, T.; et al.
Abstract : Most of the Eu compounds are in the divalent (Eu ) electronic state and order magnetically. On the other hand, the Eu-trivalent (Eu ) compounds exist but are small in number. An energy difference between the Eu and Eu states is, however, not extremely large. Therefore, the valence transition occurs in some Eu compounds. We present the characteristic properties of the Eu compounds from several viewpoints: a canting magnetisation in the Eu -antiferromagnets, the Fermi surface property in the Eu -compounds of EuPd and EuCo Si, the heavy fermion state in EuNi P, the temperature-induced valence transition in EuPd Si, the pressure-induced valence transition in EuRh Si and EuRu P, and the heavy fermion state approaching to the quantum critical point with increasing pressure in Eu Ni Ge .